Titles or Headlines? Anticipating Conclusions in Biomedical Research Article Titles as a Persuasive Journalistic Strategy to Attract Busy Readers - Jaime Sisó, Mercedes (Miscelánea: A Journal of English and American Studies, 2009)
This paper evidences the progressive adoption of a journalistic approach in title writing in certain scientific fields and suggests the reasons why this evolution has not affected all disciplines. The study is based on an analysis of 8,000 scientific research articles published over the last 25 years. The corpus was carefully selected following the advice of scientific researchers from several university departments. Factors such as the position of the journals in their impact list and the multidisciplinary or specific profile of the publication were considered. The results indicate that anticipating the conclusions in the title has become common practicein experimental works of biomedical research. An analysis of the linguistic characteristics of these conclusive titles is included to identify their basic components. It is suggested that instruction on the use of journalistic strategies is advisable for non-native writers and readers of biomedical research articles in highranking publications.
Keywords: scientific research paper titles; news value; journalistic strategies; anticipating conclusions; English for Academic Purposes